Temperament properties as a predisposition factor to the burnout syndrome occurrence in the process of teacher’s professional formation - Maltseva, Natalya V. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is due to the fact that the modern education system significantly increases the requirements for the personality of a professional and his professional skills. However, the desire to meet all the requirements presented in the process of professional development leads to great emotional, intellectual costs, strain, overwork, health problems, and the formation of negative personality traits. One of the negative formations in professional development is mental burnout syndrome. In this connection, the identification of factors determining its formation with the aim of developing prevention and correction programs to preserve the professional mental health becomes an urgent problem. to identify the temperamental properties of the occurrence of burnout syndrome in the process of professional formation of a teacher. To achieve the goal of the study, the comparative cross-sectional method, standardized methods, methods of mathematical statistics and qualitative data analysis were used. In the process of organizing and conducting the study, those temperament properties were determined, which determine the formation of such burnout components as emotional exhaustion, depersonalization and reduction of personal achievements at various stages of the teacher's professional development. the materials of the article can be useful for various specialists in the field of psychology as part of the development of special programs for the prevention of the occurrence of burnout syndrome.